PERAN PEMBELAJARAN TAHFIDZ BERBASIS METODE UMMI DALAM MEMBENTUK NILAI-NILAI KARAKTER SISWA DI SD IT HIDAYATULLAH - Rachmawati, Aisyah; Muh Wasith Achadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early cultivation of character values is an important element in basic education. One effective approach to shaping student character is through learning to memorize the Qur'an. This study aims to examine the role of tahfidz learning based on the UMMI method in shaping students' character values at SD IT Hidayatullah Yogyakarta. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations of tahfidz teachers, and program documentation. Data analysis was conducted using the Miles and Huberman model, including data reduction, presentation, and conclusion drawing. The results show that the UMMI method in tahfidz learning can instill character values systematically through structured learning stages, starting from placement tests, student grouping, murojaah process, simak-baca, to daily evaluations, volume increases, and munaqosah. The dominant character values that are formed include religion, honesty, discipline, hard work, love of reading, and innovation. This program not only targets the ability to memorize the Qur'an, but also forms students' positive behavior and habits by Islamic values. Thus, learning tahfidz based on the UMMI method is proven to play a significant role in the formation of student character values in an integrated Islamic elementary school environment. The results show that the UMMI method in tahfidz learning can instill character values through organized learning stages, such as placement exams, student grouping, murojaah process, simak-baca, daily evaluation, munaqosah, and volume improvement. Religion, honesty, discipline, hard work, love of reading, and innovation are the dominant character values. The program not only teaches students to memorize the Qur'an, but also teaches them to behave and conduct themselves in a way that is following Islamic values.